Growth and Production of Sweet Corn (Zea mays var. Saccharata) with Organic and Anorganic Fertilizer in Kendal - Qurrota Ayunin Diananda,; Lukiwati, Dwi Retno; Sutarno, (Jurnal Online Pertanian Tropik, 2020)
This study aims to examine the response of growth and production of sweet corn plants in application of organic and inorganic fertilizers. The research was conducted on July - October 2019 in Merbuh Village, Singorojo Sub-District, Kendal District and at Ecology and Plant Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang. The study used a randomized block design with 7 monofactor treatments with and each experimental unit was repeated 4 times. The treatments consisted of inorganic fertilizer (P0), chicken manure+inorganic (P1), goat manure+inorganic (P2), cow manure+inorganic (P3), chicken manure “plus’ (P4), goat manure “plus’ (P5), cow manure “plus’ (P6). Data were analyzed by variance and for treatments that showed signoficant differences further tests were carried out using DMRT at the 5% level. The observed variables were plant height, number of leaves, stalk diameter, cob production with cornhusk, and cob production without cornhusk. The results showed that the application of organic and inorganic fertilizers only affected stalk diameter. Stalk diameter in cow manure+inorganic gave the highest results compared to other treatments. There is no influence on variables observed shows that the addition of gamal leaves as a source of N-organic and phosphate rock (BP) as P-organic in manure plus (chicken, goat, cow) can be an alternative solution to substitute inorganic fertilizers (urea and TSP) on sweet corn plant.